The state and terrorism national security and the mobilization of power - Campos, Joseph H. (Homeland security, 2007)
Adopting an innovative approach to the ongoing debate over homeland security and state response to terrorism, Joseph Campos investigates the contextualizing of national security discourse and its management of terrorism. The volume incorporates historical depth and critical theory in a comparative framework to provide an invaluable insight into how national security is developed to secure the state